Kepemimpinan Kepala Sekolah dalam Meningkatkan Karakter Islami Siswa Melalui Program Tadarus Padi di SDN 01 Senduro - Veny Juliarti; Mardiyah Mardiyah; Muhammad Thohir (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to determine the role of school principals in improving Islamic character through the morning tadarus program at SDN 1 Senduro. The leadership of the school principal is the main factor in creating superior competitive schools, through good educational programs. This research uses descriptive qualitative methods to collect data through interviews, direct observation, and necessary school documents. The research results show that a school principal who is effective in improving Islamic character through this program must have a strong commitment, good managerial skills and be able to build effective communication with teachers, students and parents. The morning tadarus program at SDN 1 Senduro has succeeded in increasing student awareness and understanding of the character of Islam. Students who actively participate show an increase in more Islamic behavior. Researchers also found obstacles such as a lack of time given, and many students were still indifferent to this program. In this way, the morning tadarus program at SDN 1 Senduro is felt to have succeeded in increasing students' awareness and understanding of the teachings of Islamic character values. And it is hoped that all students can become a generation of people who care about the character of Islam in their daily lives.